Implementasi metode SDLC pada aplikasi media interaktif “EcoWatt” berbasis WebGL - Adiguna, Yogatama; Purwanto, Agus; Laksmita, Nadea Cipta (The Indonesian Journal of Computer Science, 2024)
Electrical energy is derived from the movement of electric charges due to a potential difference. Beyond housing, clothing, and food, electricity is a fundamental necessity, providing not only illumination but also powering various daily activities. Indonesia is rich in both fossil and renewable energy sources. However, the focus has predominantly been on fossil fuels, despite the fact that the electricity sector contributes 31% to global greenhouse gas emissions. Renewable energy, such as biomass, wind, water, and solar, offers sustainable alternatives. To foster early understanding and innovation in alternative energy, the author has developed "Ecowatt," a web-based educational application created using Unity and WebGL. This application aims to introduce children to the concept of alternative energy, inspiring them to develop eco-friendly energy solutions in the future. The author distributes the EcoWatt application through the website ecowatt.fun to achieve more efficient distribution, thereby fulfilling the purpose of this application's research.